The regulations of the difference between narrators of Al-Hadith - Al-Selmy, Hammad Bin Mahdy (Arab Journal for Sciences and Research Publishing, 2017)
The difference between Narrators of Hadith is considered one of the methods utilized to account for errors or discrepancies, as well as to uncover Narrators’ illusions. It is a method used by many Hadithscholars to critique narrators and their narrations. They have made many Hadith in their works according to the narrators, and it was necessary to know how to deal with these differences, and to know the purposes of the critics of their narration, and the lack of studies in this aspect, and the lack of awareness of its importance, and It consists of an introduction, two chapters and a conclusion this research is interested in this aspect, Defining the difference between narrators, Knowledge of the rules of dealing with the difference in the books of Hadith, The researcher adopted the method of collection and deduction. and reached the difference in hadith narration happens when different narrators narrate it, and it becomes ample when those narrators have many narrations. and Balancing between narrations is conducted by comparing the different narrations and critic’s perspective, due to the lack of a constant generalized rule. Hadith scholars use variety of methods to point to ‘difference’ in their books, either by a direct statement or hinting to it through the context of the chain of narrators’ reference .
Keywords: Rules; Differences; Narrators; Hadith